Robust finite-time supoptimal control of large-scale systems with interacted state and control delays - Phat, Vu Ngoc; Huong, Pham T. (Journal of Computer Science and Cybernetics, 2021)
This paper is concerned with a problem of supoptimal nite-time control for a class of linear large-scale delay systems. The system under consideration is subjected to the state and control delays interacted between subsystems. Based on improved LMI-based approach combining with new estimation techniques, we derive sucient conditions for solving nite-time H1 control and guaranteed cost control of the system. Numerical examples are given to illustrate the validity and eectiveness of the theoretical results.